Observation on different strains of Aeromonas hydrophila from various diseased fishes - Nayak, K K; Mukherjee, S C; Das, B K (Indian Journal of Fisheries, 2011)
Aeromonas hydrophila was isolated and identified from a variety of disease spectraeg. eye disease, epizootic ulcerative disease syndrome, haemorrhagic septicaemiain carps, mullets, puntius and channa. Based on its biochemical properties, it wascategorised into Kt, 1^, K,, K4 and K5 respectively. Kj strain showed negative toesculin hydrolysis whereas IC, showed positive reaction to it. Kg showed positivereaction to lysine decarboxylase as others showed negative to it and K4 showednonfermenting reaction to D-sucrose in comparison to other strains. K5 showednegative reaction to malonate as other four showed positive reaction.